Initial progress in implementing the Sustainable Development Goals (SDGs): a review of evidence from countries - Allen, Cameron; Metternicht, Graciela; Wiedmann, Thomas (Sustainability science, 2018)
The global Sustainable Development Goals (SDGs) commenced in 2016 and provide an evidence-based framework for sustainable development planning and programming until 2030. There is emerging international practice and a growing catalogue of related reviews, assessments, guidelines and publications. While the expert community is clearly emphasising the need to adopt evidence- and science-based approaches to SDG implementation, policymakers now face the challenge of implementing the SDGs simultaneously in a coherent and integrated manner. Regular systematic reviews of national progress and approaches to implementing the SDGs are advisable to ensure that emerging science and knowledge is effectively informing national practice. This paper reviews the recent academic and expert literature as well as national experience in implementing the SDGs in 26 countries. It uses a systematic approach to analyse the degree to which key implementation stages and approaches recommended in the expert literature are being adopted and applied to support national SDG implementation on-the-ground. The review highlights that while progress has been made in some initial planning stages, key gaps remain in terms of the assessment of interlinkages, trade-offs and synergies between targets. Gaps are also clearly evident in the adoption of systems thinking and integrated analytical approaches and models. This is problematic as it may undermine effective implementation and the transformative potential of the SDGs. As more countries turn their attention to the SDGs, the review underscores the considerable risk that they will pursue the same ‘siloed’ or ‘linear’ approaches to sustainable development that have met with limited success in the past.